Adeno-associated virus vector as a platform for gene therapy delivery - Wang, Dan (Nat Rev Drug Discov, 2019)
Adeno-associated virus (AAV) vectors are the leading platform for gene delivery for the treatment of a variety of human diseases. Recent advances in developing clinically desirable AAV capsids, optimizing genome designs and harnessing revolutionary biotechnologies have contributed substantially to the growth of the gene therapy field. Preclinical and clinical successes in AAV-mediated gene replacement, gene silencing and gene editing have helped AAV gain popularity as the ideal therapeutic vector, with two AAV-based therapeutics gaining regulatory approval in Europe or the United States. Continued study of AAV biology and increased understanding of the associated therapeutic challenges and limitations will build the foundation for future clinical success.